Differential patterns of postmigration HIV-1 infection acquisition among Portuguese immigrants of different geographical origins. (1st June 2022) - Pimentel, Victor Figueiredo; Pingarilho, Marta; Sole, Giordano; Alves, Daniela; Miranda, Mafalda; Diogo, Isabel; Fernandes, Sandra; Pineda-Pena, Andrea; Martins, M. Rosário O.; Camacho, Ricardo; Gomes, Perpétua; Abecasis, Ana B.
Abstract : Objective: To investigate the dynamics of phylogenetic transmission clusters involving immigrants of Portuguese Speaking Countries living in Portugal. Design/methods: We included genomic sequences, sociodemographic and clinical data from 772 HIV migrants followed in Portugal between 2001 and 2017. To reconstruct HIV-1 transmission clusters, we applied phylogenetic inference from 16 454 patients: 772 migrants, 2973 Portuguese and 12 709 global controls linked to demographic and clinical data. Transmission clusters were defined using: clusters with SH greater than 90% (phylogenetic support), genetic distance less than 3.5% and clusters that included greater than 66% of patients from one specific geographic origin compared with the total of sequences within the cluster. Logistic regression was performed to assess factors associated with clustering. Results: Three hundred and six (39.6%) of migrants were included in transmission clusters. This proportion differed substantially by region of origin [Brazil 54% vs. Portuguese Speaking African Countries (PALOPs) 36%, P  < 0.0001] and HIV-1 infecting subtype (B 52%, 43% subtype G and 32% CRF02_AG, P  < 0.001). Belonging to a transmission cluster was independently associated with treatment-naive patients, CD4 + greater than 500, with recent calendar years of sampling, origin from PALOPs and with seroconversion. Among Brazilian migrants – mainly infected with subtype B – 40.6% were infected by Portuguese. Among migrants from PALOPs – mainly infected with subtypes G and CFR02_AG – the transmission occurred predominantly within the migrants' community (53 and 80%, respectively). Conclusion: The acquisition of infection among immigrants living in Portugal differs according to the country of origin. These results can contribute to monitor the HIV epidemic and prevent new HIV infections among migrants.